Efficacy of Teak (Tectona grandis) Leaf Extract Against Aeromonas hydrophila in Catfish - Silvana Kasim; Arafik Lamadi; Indra G. Ahmad (Grouper, 2026)
Catfish is a leading commodity in the fisheries cultivation sector, one of the main problems in catfish cultivation activities is infection with Motile Aeromonas Septicemia (MAS) disease caused by the bacteria Aeromonas hydrophilla. This study aims to determine the therapeutic activity of young teak leaf (Tectona grandis) solution against Aeromonas hydrophila bacteria and to find the most effective dose of young teak leaf (Tectona grandis) solution in inhibiting the performance of Aeromonas hydrophila bacteria. using a completely randomized experimental design with 4 treatments and 3 replicates conducted over 19 days. The fish were injected intramuscularly with a concentration of 10⁶ cfu/ml (0.1 ml) and subjected to treatments A (Control), B (10 g/L), C (15 g/L), and D (20 g/L). The fish were immersed for 20 minutes. The results obtained from the study were analyzed using analysis of variance (ANOVA). The results of the study showed that herbal therapy by soaking catfish in a solution of young teak leaves was effective in treating catfish infected with A. hydrophila at the optimal dose, namely in treatment B (10 g/L), which was characterized by a decrease in the number of bacteria calculated using the ALT method of 0.06 x 10⁷ in the kidneys and 0.02 x 10⁷ in the liver, as well as a survival rate and a cure rate of 100%. The results of this study are expected to be easily implemented and beneficial for fish farmers.